2021
DOI: 10.26434/chemrxiv.13262681.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excited State Dynamics of 7-Deazaguanosine and Guanosine 5’ Monophosphate

Abstract: <p>Minor structural modifications to the DNA and RNA nucleobases have a significant effect on their excited state dynamics and electronic relaxation pathways.<b> </b>In this study, the excited state dynamics of 7-deazaguanosine and guanosine 5’-monophosphate are investigated in aqueous and in a mixture of methanol and water using femtosecond broadband transient absorption spectroscopy following excitation at 267 nm. The transient spectra are collected using photon densities that ensure no par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…2). Experimental and computational studies have showed that the first component with hundreds of femtosecond lifetime should be assigned to the effective deactivation of La state to the ground state and several conical intersections (CIs) have been identified for this process (61,62). Meanwhile, the second component of ~1.5 ps is reported to arise from vibrational cooling of the ground state by mid‐IR TA (63), which is similar to other canonical nucleobases (17,60).…”
Section: Discussionmentioning
confidence: 99%
“…2). Experimental and computational studies have showed that the first component with hundreds of femtosecond lifetime should be assigned to the effective deactivation of La state to the ground state and several conical intersections (CIs) have been identified for this process (61,62). Meanwhile, the second component of ~1.5 ps is reported to arise from vibrational cooling of the ground state by mid‐IR TA (63), which is similar to other canonical nucleobases (17,60).…”
Section: Discussionmentioning
confidence: 99%